USE OF PARTIALLY HYDROLYZED PVA FOR BORON CARBIDE SYNTHESIS FROM POLYMERIC PRECURSOR - Karaahmet, Oguz; Cicek, Bugra (UNIV CHEMISTRY & TECHNOLOGY, PRAGUE, 2020)
Boron carbide (B4C) synthesis from a polymeric precursor is an alternative to a traditional carbothermal reduction, promising low energy consumption and production costs, particularly for a polymeric precursor such as polyvinyl borate (PVBO). The sol-gel technique is preferred in the production of polymeric precursors owing to its convenience in producing single-source reactants for synthesizing B4C at low temperatures (< 1800 degrees C). The sol-gel parameters, such as the composition, viscosity, and pH, affect the formation of the polymeric precursor. In this study, industrial-grade partially hydrolyzed PVA and technical-grade boric acid (H3BO3) are used to produce PVBO. We aim to specify the viscosity and pH values for different ratios of PVA:H3BO3. A sample with a weight ratio of PVA:H3BO3 of 1:1 (PHD101) is determined to have the optimum process parameters. Calcination is performed between 500 degrees C and 700 degrees C for 1-3 h to produce a single-source reactant, which consists of boron oxide (B2O3) and carbon. It was observed that B2O3 was distributed on the nano-scale level in the carbon matrix. The reactant is heat-treated at 1400 degrees C for 5 h and crystalline, polyhedral, and irregular B4C particles are synthesized at low temperatures from industrial grade raw materials.
Keywords: Industrial raw materials; Sol-gel; pH; Composition ratio; Single-source reactant; Low temperature; Boron Carbide (B4C); Hydrolyzed PVA; LOW-TEMPERATURE SYNTHESIS; POLY(VINYL ALCOHOL); POWDER; ACID; B4C; MICROSTRUCTURE; PARAMETERS; TOUGHNESS; HARDNESS; PRODUCT; Materials Science